Comparative Transcriptomics Reveals the Key lncRNA and mRNA of Sunite Sheep Adrenal Gland Affecting Seasonal Reproduction - Du, Xiaolong; He, Xiaoyun; Liu, Qiuyue; Di, Ran; Liu, Qingqing; Chu, Mingxing (Frontiers in Veterinary Science, 2022)
The hypothalamic–pituitary–adrenal (HPA) axis plays an important role in the growth and development of mammals. Recently, lncRNA transcripts have emerged as an area of importance in sheep photoperiod and seasonal estrus studies. This research aims to identify lncRNA and mRNA that are differentially expressed in the sheep adrenal gland in long (LP) or short (SP) photoperiods using transcriptome sequencing and bioinformatics analysis based on the OVX+E2 (Bilateral ovariectomy and estradiol-implanted) model. We found significant differences in the expression of lncRNAs in LP42 (where LP is for 42 days) vs. SP-LP42 (where SP is for 42 days followed by LP for 42 days) (n = 304), SP42 (where SP is for 42 days) vs. SP-LP42 (n = 1110) and SP42 vs. LP42 (n = 928). Cluster analysis and enrichment analysis identified SP42 vs. LP42 as comparable group of interest and found the following candidate genes related to reproductive phenotype: FGF16, PLGF, CDKN1A, SEMA7A, EDG1, CACNA1C and ADCY5. FGF16 (Up-regulated lncRNA MSTRG.242136 and MSTRG.236582) is the only up-regulated gene that is closely related to oocyte maturation. However, EDG1 (Down-regulated lncRNA MSTRG.43609) and CACNA1C may be related to precocious puberty in sheep. PLGF (Down-regulated lncRNA MSTRG.146618 and MSTRG.247208) and CDKN1A (Up-regulated lncRNA MSTRG.203610 and MSTRG.129663) are involved in the growth and differentiation of placental and retinal vessels, and SEMA7A (Up-regulated lncRNA MSTRG.250579) is essential for the development of gonadotropin-releasing hormone (GnRH) neurons. These results identify novel candidate genes that may regulate sheep seasonality and may lead to new methods for the management of sheep reproduction. This study provides a basis for further explanation of the basic molecular mechanism of adrenal gland, but also provides a new idea for a comprehensive understanding of seasonal estrus characteristics in Sunite sheep.